Critical Events in the Ethics of U.S. Corporation History - Beets, S. Douglas (2011)
The history of corporations in the United States (U.S.) is much older than the country, as it must be understood in the context of the history of peoples of Europe who eventually dominated the North American continent in the seventeenth and eighteenth centuries. These European settlers came, in part, to achieve economic prosperity for themselves and, in many cases, for early forerunners of the modern corporation. These business organizations had predecessors in Europe millennia earlier as ancient Romans had developed a functional and successful form of corporation for the purpose of conducting commerce in the Roman Empire. In the decades that followed the founding of the U.S. in 1776, corporations evolved from rare, small, closely controlled business organizations with a multitude of restrictions to very large, very powerful modern institutions that enjoy many of the legal rights of humans. With this evolution came ethical issues, as (1) the ethical distance was altered between corporate decision-makers and those affected by those decisions, and (2) many of the legal rights of individual humans were extended, through litigation, to corporations. This article explains the historical development of the U.S. corporation and identifies 20 Critical Events in the Ethics of Corporation History (CEECH). An understanding of these historical events may facilitate comprehension of many of the current ethical issues associated with a legal organizational form that profoundly affects business and society.
Keywords: Regulation; Personhood; History; Ethics; Corporation